Lymphocyte Variation in Peripheral Blood of Mice with Low Level Gamma Irradiation - Waghmare, Girish (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Series of studies were conducted to explore the effects of gamma irradiation to peripheral blood of male Swiss albino mice. Radioprotection was evaluated by the ability of Liv 52 to reduce the lethality produced by cobalt-60 gamma radiation. Mice were treated by oral gavage once daily for seven consecutive days with Liv 52 (500 mg/kg body weight) prior to radiation.Male Swiss albino mice were exposed to 1 and 3 Gy of whole-body gamma irradiation in the presence (experimental) and absence (control) of a herbomineral formulation of Liv.52. Quantitative variations in the number of total leukocytes count (TLC), lymphocytes and neutrophils were scored in peripheral blood at various time intervals between on the day of exposure to 28 days. At 1Gy dose, depression in TLC was noticed till day 1, whereas in higher doses until day 5 with a sharpness in first 24 hrs. Prior administration of Liv.52 significantly prevented the depletion of leukocytes count and initiated recovery towards normal at 28 days in experimental animal. The behaviour of neutrophils was reciprocal as they showed rise till day 1 followed by gradual decline up to day 5 in control (without liv 52) as well as in experimental group with both the irradiation doses. It is noted that liv 52 decreases the direct cell killing against gamma radiation may be due to by increasing the cellular glutathione (GSH) level [16] and restores early recovery of lymphocyte in drug treated animal. Key words: Differential leukocytes count, Mice, Liv.52, Gamma Rays, Radioprotection.